Case Report: Congenital absence of the fifth metacarpal with polydactyly and syndactyly - Qin, Zhihong; Luo, Xiaolin; Ding, Xiaofei; Liao, Shijie (Frontiers in Pediatrics, 2025)
Congenital hand malformations encompass various types, with polydactyly and syndactyly being common. However, congenital absence of the metacarpal is rarely reported, and literature on this condition remains limited. To date, no cases of congenital absence of the fifth metacarpal combined with polydactyly and syndactyly have been documented. Here, we present a case of a 7-month-old female infant with congenital absence of the fifth metacarpal accompanied by polydactyly and syndactyly. The intraoperative management strategy is described, and early postoperative outcomes are evaluated. This case report aims to provide treatment approaches and clinical experience for complex congenital hand malformations, offering reference for clinicians managing similar cases in the future.